An alternative mode to activate alcohols: application to the synthesis of N-heteroarene derivatives. Issue 18 (21st July 2021) - Liu, Xiaoping; Sotiropoulos, Jean-Marc; Taillefer, Marc
Abstract : Activation of primary alcohols in the presence of KO t Bu/DMF allowed the synthesis of N -heteroarenes via the alkylation of the C(sp 3 )–H bond of methyl azaarenes. A mechanism involving the formation of an alkyl formate intermediate is proposed. Abstract : The activation of readily available but poorly reactive alcohols can be carried out solely in the presence of the tert -butoxide (KO t Bu)/dimethylformamide (DMF) couple. This system allows the direct use of primary alcohols as alkylating agents to functionalize the C(sp 3 )–H bond of methyl azaarenes, in the absence of traditionally used transition metal-based catalysts. Various alkylated N-heteroarenes such as pyridine, quinoline, pyrazine or quinoxaline derivatives have been obtained by this method, which is supposed to proceed via the initial formation of an alkyl formate intermediate, as shown by experimental and theoretical mechanistic studies.